Testicular development and endocrine function in boars fed altrenogest - Kluber, E.F. III; Minton, J. Ernest; Stevenson, Jeffrey S.; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Crossbred male pigs were used to evaluate the influence of a synthetic progestogen on reproductive development. Concentrations of luteinizing hormone (LH) and testosterone in blood serum were reduced while boars were being fed altrenogest (15 to 21 wk of age). At 25 wk of age (4 wk after withdrawal from altrenogest), weights of the testes and accessory reproductive glands and testicular content of sperm were reduced in boars that had been fed altrenogest. However, testicular weight and content of sperm had returned to control values following 12 wk after withdrawal from altrenogest. In addition, concentration of LH and testosterone in blood serum were similar for control boars and boars previously fed altrenogest. We conclude that suppression of normal reproductive development of growing boars by altrenogest merely delays the onset of sexual maturation but does not permanently affect testicular function.
Keywords: Swine; Testicular development; Endocrine; Altrenogest